İnformal Eğitim Süresince Öğrencilerin Teknolojiye Dayalı Kazanımlarının Belirlenmesi / Determination of Technology Based Gains of Students During Informal Education - Bekar, Makbulenur; Sadıklar, Zeynep; Küçük Karakaş, Bahar; Camiz, Alessandro (Journal of History Culture and Art Research, 2018)
ABSTRACT Design studios have a multi-layered and integrative structure that involves different thinking and learning approaches. Outcomes are quite numerous and diverse in terms of the students. Therefore, various seminars, workshops, and many other events are organized by universities for this purpose in the education process. These activities help students to be successful in both the educational process and the business life. In this process, developing and changing technology has entered into education processes and has become a part of education. Thus, over time, the use of technology, as well as traditional methods, has become a necessity in architectural education institutions. Lessons with digital technologies have been added to current course contents. For students, these technologies are used as subsidiary tools in making the presentations. The international research and design seminar and workshop activity was held in Kyrenia on May 6-13, 2018, was organised by the Girne American University (GAU) Department of Interior Architecture and the International Centre for Heritage Studies for the first time. The event was carried out in collaboration with the University of Florence, the Sapienza University of Rome, the Özyeğin University and the Department of Antiquities and Museums (TRNC). The workshop consists of 11 scientific committee members1, 7 scientific coordinators2, 5 organization committee members3 and 16 studio trainers4, who observed and led the process and studies during 8 days. The workshop trainers consist of 16 faculty member and PhD students totally, 13 of whom are from these universities and 35 of whom are from the Karadeniz Technical University. The aim of this study is to measure and evaluate the technological achievements provided to the students through this international workshop activity. The survey technique was used to find out what extent students benefit from the technology while expressing their projects and to question the achievements based on the technology through the workshop activity. The survey was conducted with 36 students who participated in this event. In the direction of the survey results, the most effective factors and variables were determined to put forward the technology achievements on the students. At the end of the study, the achievements of the students from the workshop activity, one of the informal training methods, were examined. SPSS 23.0 program was used for the statistical analyzes, which is based on the data of the survey. ÖZ Tasarım atölyeleri farklı düşünme ve öğrenme yaklaşımlarını barındıran çok katmanlı ve bütüncül bir yapıya sahiptir. Kazanımları ise öğrenciler açısından oldukça fazla ve çeşitlidir. Bu amaçla eğitim sürecinde, çeşitli seminerler, atölye çalışmaları ve daha benzeri birçok etkinlik üniversitelerce düzenlenmektedir. Bu etkinlikler öğrencilerin, hem eğitim sürecinde hem de iş hayatında başarılı olabilmelerine yardımcı olmaktadır. Bu süreçte gelişen ve değişen teknoloji eğitim süreçlerine de girmiş ve eğitimin bir parçası haline gelmiştir. Böylece mimarlık eğitim kurumlarında zamanla geleneksel yöntemlerin yanında teknoloji kullanımı bir ihtiyaç haline gelmiştir. Mevcut ders içeriklerine dijital teknolojileri içeren dersler eklenmiştir. Bu teknolojiler ise, öğrencilerin sunumlarını gerçekleştirmelerinde, yardımcı araçlar olarak kullanılmaktadır. 6-13 Mayıs 2018 tarihinde Girne’de gerçekleşen ‘Reading and Designing the Kyrenia Castle: Enhancing Heritage in The Historical Landscape’ uluslararası araştırma, tasarım semineri ve atölye etkinliği, Girne Amerikan Üniversitesi (GAU) İç Mimarlık Bölümü ve Uluslararası Kültürel Miras Çalışmaları Merkezi tarafından ilk kez düzenlenmiştir. Etkinlik, Floransa Üniversitesi, Roma Sapienza Üniversitesi, Özyeğin Üniversitesi ve Eski Eserler ve Müzeler Dairesi (KKTC) işbirliği ile gerçekleştirilmiştir. 11 bilimsel komite üyesi, 7 bilimsel koordinatör, 5 organizasyon komitesi üyesi ve 16 stüdyo eğitmeni tarafından yapılan atölye çalışması, 8 günlük gözlem, deneyim ve uygulama sürecini kapsamaktadır. Atölye eğitmenleri, söz konusu üniversitelerden 13, Karadeniz Teknik Üniversitesi’nden 3 olmak üzere toplam 16 öğretim elemanı ve doktora öğrencisinden oluşmaktadır. Yapılan bu çalışmanın amacı, gerçekleştirilen uluslararası etkinliğin öğrencilere sağladığı teknolojiye dayalı kazanımların ölçülmesi ve değerlendirilmesidir. Atölye çalışmaları sürecinde öğrencilerin projelerini ifade etme biçimlerinde teknolojiden ne derece yararlandıkları ve teknolojiye dayalı kazanımlarının sorgulanması için anket (survey) tekniği kullanılmıştır. Anket çalışması etkinliğe katılan 36 öğrenci ile gerçekleştirilmiştir. Anket sonuçları doğrultusunda etkinliğin öğrenciler üzerindeki teknoloji kazanımlarını belirlemede en etkili faktörler ve değişkenler ortaya konulmaya çalışılmıştır. Çalışmanın son aşamasında, informal eğitim metotlarından biri olan atölye çalışmasından öğrencilerin teknolojiye dayalı kazanımları irdelenmiştir. Araştırmada oluşturulan verilerle gerçekleştirilen istatistiksel analizler için SPSS 23.0 programı kullanılmıştır.